Linguistic Features of Ergonims Representing Farming - Nuriddinova Nozima Avazxonovna (International Journal on Integrated Education, 2022)
This article widely covers the linguistic features of ergonyms denoting a farm. Ergonyms are a mirror of the national culture, contain a large amount of information about traditions, customs, mentality and the world perception peculiarities, specific to this or that linguistic community in a given period. The article is devoted to the issue of creating a separate class of ergonyms – service names, which in the structure of the onomastic space of the language act as the names of farming in the Republic of Uzbekistan.